AB0741 Detection of Psoriatic Arthritis in Patients with Psoriasis in Daily Routine Care Using Questionnaires for Diagnosis of Psoriatic Arthritis and Fluorescence-Optical Imaging Technique: Diagnostic Value for Detection of Subclinical Signs of Musculoskeletal Inflammation in Psoriasis?. (15th July 2016) - Köhm, M.; Rossmanith, T.; Langer, H.-E.; Burmester, G.; Wassenberg, S.; Kaesser, U.; Backhaus, M.; Burkhardt, H.; Behrens, F.; ,
Abstract : Background: Psoriasis (Pso) is one of the most common chronic inflammatory skin disease in Europe. Psoriatic arthritis (PsA) is closely associated to Pso; the skin manifestation appears usually years before PsA-related symptoms emerge. Up to 30% of Pso patients develop PsA; its concrete prevalence is still unclear. Questionnaires for detection of PsA (PASE, PEST, GEPARD) are validated tools for use in dermatology practice with different sensitivity and specificity levels. Fluorescence-optical imaging technique is a new method to detect changes in microvascularisation of the hands as potential early marker for subclinical musculoskeletal inflammation. Positive results of screening questionnaires in patients without current detection of PsA in rheumatological examination might have a diagnostic value to reflect subclinical disease activity of PsA. Methods: This interims analysis includes 151 Pso patients (diagnosis confirmed by dermatologist) without pre-existing diagnosis of PsA but risk factors for its development (nail psoriasis and/or joint pain or swelling within the last 6 months) from a prospective, multicentre study (XCITING) in Germany. Patients are examined by rheumatologist (clinical examination and ultrasound) to determine PsA-diagnosis. FOI is performed additionally and analysed by an independent central reader. Results for PASE, PEST and GEPARD questionnaires as well as for FOI in comparison to the diagnosis of PsA by rheumatologist are compared to survey their value for clinical performance. Results: In 81 out of 151 (53.6%) psoriasis patients with risk of development of PsA (as defined in inclusion criteria) PsA was diagnosed by rheumatologist using clinical examination and ultrasound. PsA confirmed patients were positive in 71.6% when using PASE, 32.1% when using PEST and 44.4% by GEPARD. Positive results in questionnaires despite negative results in rheumatologists assessment were seen in 28.4 – 67.9% of the used tools (67.9% PASE, 28.4% PEST, 55.6% GEPARD). In addition to PsA confirmed by rheumatologists, in 23.2% of Pso patients without clinical verified PsA a positive FOI-signal could be detected. In this group PASE was positive in 47.1%, PEST in 14.3% and GEPARD in 25.7% of the patients. Conclusions: In this cohort of patients with active Pso and newly diagnosed PsA but with pre-defined risk of development of PsA, more than 50% of the patients were classified as PsA by rheumatologist. The sensitivity of detection of PsA by using questionnaires in early disease seems to be limited. False positive results in questionnaires in patients without clinical evident PsA might be influenced by signs of subclinical inflammation measured by FOI. Disclosure of Interest: M. Köhm Grant/research support from: Pfizer, T. Rossmanith Grant/research support from: Pfizer, H.-E. Langer Grant/research support from: Pfizer, G. Burmester Grant/research support from: Pfizer, S. Wassenberg Grant/research support from: Pfizer, U. Kaesser Grant/research support from: Pfizer, M. Backhaus Grant/research support from: Pfizer, H. Burkhardt Grant/research support from: Pfizer, F. Behrens Grant/research support from: Pfizer